Production of bio-oil from sawdust and oil palm fronds biomass uaing gas fired pyrolysis system - Nur Idayu, Nirda Ismail (2012)
Fast pyrolysis of biomass is the most promising technology of exchanging solid biomass to liquid bio-oil as a renewable substitution of fossil resources in fuel and chemical feedstock’spurposes.Malaysia with abundant biomass resources allows an ideal platform for the growth of this thermal conversion technology.Biomass fast pyrolysis is rapidly developing interest in Malaysia as it is considered to offer efficient logistical and hence economic advantages over other thermal conversion process.In this study,pyrolysis of sawdust and oil palm fronds were investigated under various heat distribution and pyrolysis temperature in gas fired reactor.The heat distribution was done in different setting of fuel and air of gas burner. The setting are 16mbar of fuel with 7.5 air,19mbar of fuel with 2.5 air and 19mbar of fuel with 5.0 air.The best setting of fuel and air ratio is the setting 19mbar of fuel with 2.5 air ratio where it give shortest time to reach 400oC of the temperature of the reactor.The temperatures of pyrolysis were varied in range of 400oC-600oC.The products obtained from pyrolysis of waste furniture sawdust and palm oil stem were bio-oil,char and gas.The maximum bio-oil yield was obtained at temperature 500oC.This study provides better insight on heat distribution and temperature of the reactor.